The dynamics of pepsinogens plasma levels in cardiosurgical patients with erosive and ulcerous changes of the gastroduodenal area - Ye. A. Sorokina; V. B. Loyenko; N. A. Morova; S. A. Kopeikin; V. V. Safechuk; N. A. Levitskaya (Бюллетень сибирской медицины, 2012)
The pepsinogenemia level is examined as a risk factor of atrophy and inflammation activity in gastroduodenal region mucous region in 20 patients with erosive and ulcerous changes this localization as before as after operations with cardiopulmonary bypass. It is marked that the values of pepsinogen 1 ((209,58 ± 14,41) μg/l) and pepsinogen 1 ((30,01 ± 4,00) μg/l) in plasma are exceeded than normal magnitudes. It is revealed that using omeprazole intravenous and peroral after that can prevent of acute ulcers and gastric bleeding in these patients and associated with decrease of pepsinogen 1 (in 1,2 times) and pepsinogen 2 (in 2,1 times) plasma levels comparing values before operation. In spite of acute ulcers and gastroduodenal bleeding default, gastropaty with erosions in antrum of stomach persists in 35% of cardiosurgical patiewnts.